Determinan Kematian Neonatal di Rumah Sakit Ibu dan Anak Aceh - Nurhayati, Nurhayati; Abdullah, Asnawi; Maidar, Maidar; Hermansyah, Hermansyah; Zakaria, Radhiah (LPPM Hang Tuah Pekanbaru, 2024)
Neonatal mortality is an important issue to receive attention because neonatal death not only affects infant mortality rates but also has an impact on society. This research wants to examine the determinants of neonatal death in the Mother and Child Hospital (RSIA) Aceh. This type of research is analytic with a case-control design. The case population in this study were all babies who were born and died at the age of 0-28 days, both those born at the Aceh Mother and Child Hospital (RSIA) and those referred to the Aceh Mother and Child Hospital (RSIA) from January to October 2022. totaling 108 people. The sample in this study was 216 babies consisting of 108 case babies and 108 control babies. Data analysis used a logistic regression test. The results showed that the factors that had a significant value (P value <0.05) with neonatal mortality were low birth weight (OR= 5.5; 95% CI 2.35 – 12.23), premature (OR= 0.36; 95% CI 0.13 – 0.96), jaundice (OR= 0.20; 95% CI 0.09 – 0.43), and sepsis (OR= 9; 95% CI 4.41 – 20.89), age mother > 35 years (OR 0.43; 95% CI 0.19 – 0.94), neonatal referral (OR= 0.01; 95% CI 0.00 – 0.17) and long-distance ANC (OR= 6 .6; 95% CI 2.82 – 15.63), length of stay in the emergency room ≥ 30 minutes (OR= 0.15; 95% CI 0.73 – 0.31), length of stay 1-5 days (OR= 4.3; 95% CI 2.17 – 8.78). This study concludes that sepsis is the most associated factor with neonatal mortality in RSIA. It is recommended that related parties to improve the quality of ANC services according to standards and improve the quality of PONEK (Comprehensive Emergency Neonatal Midwifery Services).